2010
DOI: 10.1001/jama.2010.1361
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism and the Risk of Coronary Heart Disease and Mortality

Abstract: for the Thyroid Studies Collaboration C ONTROVERSY PERSISTS ON THEindications for screening and threshold levels of thyroidstimulating hormone (TSH) for treatment of subclinical hypothyroidism, 1-3 defined as elevated serum TSH levels with normal thyroxine (T 4 ) concentrations. Because subclinical hypothyroidism has been associated with hypercholesterolemia 4 and atherosclerosis, 5 screening and treatment have been advocated to prevent cardiovascular disease. 3 However, data on the associations with coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
813
7
56

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,021 publications
(942 citation statements)
references
References 48 publications
37
813
7
56
Order By: Relevance
“…Although these results are less comparable because of different characteristics of participants in the different studies, we found a regression rate higher than most previous studies in our study, which was the only one to enroll only patients with mild SCH from both sexes. Based on previous studies and expert reviews, we used 7.0 mIU/L of TSH as cut-off points [1,13] and found that higher TSH concentrations significantly impaired the likelihood of TSH normalization in our logistic regression analysis, similar to previous studies [6,8,10]. Accordingly, the generally lower TSH levels among our cases compared with previous studies may be one of the reasons that TSH normalization occurred in a high proportion of our patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although these results are less comparable because of different characteristics of participants in the different studies, we found a regression rate higher than most previous studies in our study, which was the only one to enroll only patients with mild SCH from both sexes. Based on previous studies and expert reviews, we used 7.0 mIU/L of TSH as cut-off points [1,13] and found that higher TSH concentrations significantly impaired the likelihood of TSH normalization in our logistic regression analysis, similar to previous studies [6,8,10]. Accordingly, the generally lower TSH levels among our cases compared with previous studies may be one of the reasons that TSH normalization occurred in a high proportion of our patients.…”
Section: Discussionsupporting
confidence: 74%
“…SCH was defined as a combination of elevated TSH and normal FT4, and classified into mild or severe when TSH ≤10 mIU/L or >10 mIU/L, respectively [4]. Positivity for TPOAb was considered when the serum mortality in those with higher TSH levels [13]. Other possible adverse consequences include depression, Alzheimer disease, the worsening of renal function in patients with chronic kidney diseases (CKD), symptomatic OH and disordered lipid metabolism, particularly elevation of total cholesterol (TC) [2,4].…”
Section: Anthropometric Measurements and Laboratory Methodsmentioning
confidence: 99%
“…A systematic review of 13 heterogeneous studies has demonstrated the effect of substitution therapy with Levothyroxine at SH on reducing the concentrations of LDL cholesterol and total cholesterol [7]. Similar results have been demonstrated in other RCTs [8].…”
Section: Discussionsupporting
confidence: 56%
“…On the background of substitution therapy with Levothyroxine in patients with SH a decrease of carotid arteries intima-media thickness [6], an improvement of endothelial function [5], improvement of cardiac function [4] were observed. Such therapy may reduce the risk of coronary heart disease in relatively young patients with SH, but not in people aged over 70 years [8]. Adequate RCTs devoted to the study of cardiovascular events in the renew of euthyroidism is still few.…”
Section: Discussionmentioning
confidence: 99%
“…Although elevated TSH in older adults was found to be associated with decreased mortality [3], there is a great body of literature that suggests many negative effects of elevated TSH on health. It was found to be associated with cardiac dysfunction [4], higher low-density lipoprotein cholesterol [5]. Some studies even found association with depression and cognitive dysfunction [6] although the evidence for this is not conclusive [7].…”
Section: Introductionmentioning
confidence: 99%